The potential of effector‐target genes in breeding for plant innate immunity. Issue 3 (27th December 2012) - Gawehns, Fleur; Cornelissen, Ben J. C.; Takken, Frank L. W.
Summary Increasing numbers of infectious crop diseases that are caused by fungi and oomycetes urge the need to develop alternative strategies for resistance breeding. As an alternative for the use of resistance (R) genes, the application of mutant susceptibility (S) genes has been proposed as a potentially more durable type of resistance. Identification of S genes is hampered by their recessive nature. Here we explore the use of pathogen‐derived effectors as molecular probes to identify S genes. Effectors manipulate specific host processes thereby contributing to disease. Effector targets might therefore represent S genes. Indeed, the Pseudomonas syringae effector HopZ2 was found to target MLO2, an Arabidopsis thaliana homologue of the barley S gene Mlo. Unfortunately, most effector targets identified so far are not applicable as S genes due to detrimental effects they have on other traits. However, some effector targets such as Mlo are successfully used, and with the increase in numbers of effector targets being identified, the numbers of S genes that can be used in resistance breeding will rise as well.